Crisis in Detail. On the article “The crisis of a detail as a detail of the crisis” by E. Bagina - Петр Капустин (Проект Байкал, 2023)
The present text is a response to the article “The crisis of a detail as a detail of the crisis” by E. Yu. Bagina included in the current issue of the journal. The author expresses his point of view on the important questions raised in the article.